But really, how are you ? : a courageous journey within the heart and how to live fearlessly - Abu Samaha, Rana (Passionpreneur Publishing, 2020)
Not many have the courage to enter this world with the curiosity of a child and use loss, grief, and fear as their catalyst for change. It is not unusual to be afraid of showing the world our true selves, especially when we are surrounded by judgments in our daily lives.If you want to discover how you really feel and understand who you truly are, NOW is the time to stop, pause, and listen to your inner child. This book helps you explore yourself, understand your feelings, and know the real you. Guided by personal lessons and tips from the author's life experiences, and a dedicated journal with a section for reflection at the end of each stepping stone, you will be encouraged to discover your voice, your courageous authentic-self, and lead with love. You can let fear move you forward in your quest of living and will finally be able to answer the question "But REALLY, How Are You?" truthfully and courageously.